2000
DOI: 10.1292/jvms.62.789
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Contamination in Commercial Layer Feed in Japan.

Abstract: ABSTRACT. A total of 4,418 samples of commercial layer feeds obtained in 1998 were investigated for the presence of salmonellae. A total of 146 strains of salmonellae which consisted of 32 serovars, including 20 strains of Salmonella Enteritidis, were isolated from 143 feed samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…is a serious threat to consumer health due to its ability to adapt to many different environments and broad range of transmission routes producing acute and chronic infections in all or most types of birds and animals (Bains 1979, Mallinson 1984, Barnes et al, 2003, Maciorowski et al, 2004. According to Shirota et al (2001) broiler and layer feed is one of the important sources of chicken farm contaminated with Salmonella. The result of poultry inoculation in this study revealed that lower dose (2.68x10…”
Section: Discussionmentioning
confidence: 99%
“…is a serious threat to consumer health due to its ability to adapt to many different environments and broad range of transmission routes producing acute and chronic infections in all or most types of birds and animals (Bains 1979, Mallinson 1984, Barnes et al, 2003, Maciorowski et al, 2004. According to Shirota et al (2001) broiler and layer feed is one of the important sources of chicken farm contaminated with Salmonella. The result of poultry inoculation in this study revealed that lower dose (2.68x10…”
Section: Discussionmentioning
confidence: 99%
“…24 At last, other risk factors which were not considered in the present study are important to 1 mention. For example, it could be useful to build a model taking into account flock 2 characteristics (type of breed, number of flocks on the farm, multi-age farm or not), farm 3 management (control of pest access, visitors allowed or not, feed composition and feeding 4 practices, drinking water), cleaning and disinfecting practices related with the contamination 5 status of the previous flock in the same hen house ( ( Henzler & Opitz, 1992;Kinde et al, 6 1996;Shirota et al, 2000;Garber et al, 2003;Liebana et al, 2003;Kinde et al, 2005). 7…”
Section: Discussionmentioning
confidence: 99%
“…Six isolates of Salmonella from 37 (16.2%) imported broiler fish meal were recovered [19] and mash feed contains fish and meat and bone meals mostly used for layer breeder were far more frequent 21% and 4% respectively [20] contaminated with Salmonella. Broiler and layer feed is one of the important sources of chicken farm contaminated with Salmonella [21].…”
Section: Presence or Absence Enumeration And Percentage Of Salmonellmentioning
confidence: 99%